When distance drives destination, towns can stimulate development - Joachim De Weerdt; Luc J. Christiaensen; Ravi Kanbur (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2021)
While city migrants see their welfare increase much more than those moving to towns, many more rural-urban migrants end up in towns. This phenomenon, documented in detail in Kagera, Tanzania, begs the question why migrants move to seemingly suboptimal destinations. Using an 18-year panel of individuals from this region and information on the possible destinations from the census, this study documents, through dyadic regressions and controlling for individual heterogeneity, how the deterrence of further distance to cities (compared to towns) largely trumps the attraction from their promise of greater wealth, making towns more appealing destinations. Education mitigates these effects (lesser deterrence from distance; greater attraction from wealth), while poverty reduces the attraction of wealth, consistent with the notion of urban sorting. With about two thirds of the rural population in low-income countries living within two hours from a town, these findings underscore the importance of vibrant towns for inclusive development.
Keywords: J61; O15; O55; 330; Africa; internal migration; urbanization; secondary towns